Phosphonate-titanium dioxide assemblies: platform for multimodal diagnostic-therapeutic nanoprobes - Řehoř, Ivan; Vilímová, Vanda; Jendelová, Pavla; Kubíček, Vojtěch; Jirák, Daniel; Herynek, Vít; Kapcalová, Miroslava; Kotek, Jan; Černý, Jan; Hermann, Petr; Lukeš, Ivan (Journal of medicinal chemistry, 2011)
Multimodal imaging-therapeutic nanoprobe TiO(2)@RhdGd was prepared and successfully used for in vitro and in vivo cell tracking as well as for killing of cancer cells in vitro. TiO(2) nanoparticles were used as a core for phosphonic acid modified functionalities, responsible for contrast in MRI and optical imaging. The probe shows high (1)H relaxivity and relaxivity density values. Presence of fluorescent dye allows for visualization by means of fluorescence microscopy. The applicability of the probe was studied, using mesenchymal stem cells, cancer HeLa cells, and T-lymphocytes. The probe did not exhibit toxicity in any of these systems. Labeled cells were successfully visualized in vitro by means of fluorescence microscopy and MRI. Furthermore, it was shown that the probe TiO(2)@RhdGd can be changed into a cancer cell killer upon UV light irradiation. The above stated results represent a valuable proof of a principle showing applicability of the probe design for diagnosis and therapy.
Keywords: Phosphorous Acids; Animals; HeLa Cells; Magnetic Resonance Imaging; Fluorescent Dyes; mezenchymální kmenové buňky; Microscopy, Fluorescence; afinitní značky; screeningové testy protinádorových léčiv; Nanoparticles; Structure-Activity Relationship; lidé; HeLa buňky; Titanium; Antineoplastic Agents; Mice; protinádorové látky; komplexní sloučeniny; magnetická rezonanční tomografie; Ultraviolet Rays; Affinity Labels; fluorescenční barviva; nanočástice; fluorescenční mikroskopie; T-lymfocyty; myši; titan; Coordination Complexes; Mesenchymal Stem Cells; kyseliny fosforité; gadolinium; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Cell Survival; T-Lymphocytes; zvířata; viabilita buněk; Gadolinium; ultrafialové záření; Humans